2022
DOI: 10.3390/catal12121513
|View full text |Cite
|
Sign up to set email alerts
|

Post-Synthesis Strategies to Prepare Mesostructured and Hierarchical Silicates for Liquid Phase Catalytic Epoxidation

Abstract: Olefin epoxidation is an important transformation for the chemical valorization of olefins, which may derive from renewable sources or domestic/industrial waste. Different post-synthesis strategies were employed to introduce molybdenum species into mesostructured and hierarchical micro-mesoporous catalysts of the type TUD-1 and BEA, respectively, to confer epoxidation activity for the conversion of relatively bulky olefins (e.g., biobased methyl oleate, DL-limonene) to epoxide products, using tert-butyl hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Pristine silica TUD-1 was prepared in a similar fashion, but without the Nb 2 O 5 nanoparticles, as described in the literature. 71…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pristine silica TUD-1 was prepared in a similar fashion, but without the Nb 2 O 5 nanoparticles, as described in the literature. 71…”
Section: Methodsmentioning
confidence: 99%
“…The textural properties were somewhat comparable to those of the mesoporous silica TUD-1 (synthesized in a similar fashion, but without Nb 2 O 5 ) which possessed S BET = 471 m 2 g −1 and d p = 8.5 nm. 71…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature survey for Mo-containing silica/silicates tested in the epoxidation of MeOle or MeLin, indicated two previous studies. 104,105 Gao et al 105 reported the epoxidation of MeOle with H 2 O 2 , in the presence of molybdenum supported on the external surface of TS-1, which led to ca. 65% MeOleEp selectivity at ca.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%